Coupled effect of particle size of the source materials and calcination temperature on the direct synthesis of hydroxyapatite. Issue 9 (8th September 2021) - Hossain, Md. Sahadat; Mahmud, Monika; Sultana, Sazia; Bin Mobarak, Mashrafi; Islam, M. Saiful; Ahmed, Samina
Abstract : We report the effect of controlled particle size (obtained by using 80, 100, 120, 140 and 200 mesh) of the source materials on the synthesis of a well-known biomaterial, hydroxyapatite (Hap). In addition to this, we have also mapped the consequence of applied temperature (700°C, 800°C and 900°C) on the crystallographic properties and phase composition of the obtained Hap. Nevertheless, although with Hap, in each case, β-tricalcium phosphate (β-TCP) was registered as the secondary phase the ANOVA test revealed that the results of the crystallographic parameters are significantly different for the applied sintering temperature 700°C and 800°C ( p < 0.05), while the data obtained for calcination temperature 800°C are not significantly different from that acquired at 900°C ( p > 0.05). Fourier transform infrared spectrophotometer data ensured that, irrespective of mesh size and calcination temperature, the synthesized Hap samples were of carbonated apatite with B-type substitution. Interestingly, for all cases, the % of carbonate content was below the maximum limit (8%) of the CO 3 2 − ion present in bone tissue hydroxyapatite.